Egyszerű egyenletek

1.Oldd meg a következő egyenleteket!

x + 7 = 2x + 6 x + 6 = 3x + 9 x - 8 = 2x - 1
4x - 1 = x + 3 3x - 3 = x + 2 2x + 2 = x + 4
4x - 6 = 5x - 3 5x - 1 = 5x - 9 3x + 4 = 2x - 1
2x + 7 = 7x + 8 2x - 9 = 7x + 3 5x + 2 = 4x - 6
6x - 7 = 5x + 9 5x + 7 = 2x - 1 5x + 1 = 6x + 1
6x + 1 = 7x + 8 4x + 9 = 6x - 6 2x + 8 = 7x - 7

2.Oldd meg a következő egyenleteket!

4·(4x + 7) = 15 4·(6x - 3) = 7 4·(3x - 2) = -18
4·(5x - 6) = 14 4·(6x + 6) = 13 4·(7x + 6) = -6
3·(2x - 7) = -8 3·(5x - 2) = 4 -3·(7x + 8) = -15

3.Oldd meg a következő egyenleteket!

2·(6x - 2) = 3·(5x - 3) - 15 4·(7x + 5) = 4·(4x + 6) + 5
4·(5x - 7) = 3·(4x + 2) - 11 3·(3x + 8) = 3·(7x + 2) + 17
4·(6x - 6) = 4·(6x + 7) + 11 -2·(2x - 5) = 2·(3x - 8) + 11

4.Oldd meg a következő egyenleteket!

4·(3x - 7) - 4·(7x - 4) = 2·(8x - 3) - 10 2·(7x - 5) + 3·(3x - 6) = 2·(8x + 8) - 14
2·(2x + 4) + 4·(8x + 8) = 3·(8x + 2) - 2 4·(8x + 8) + 3·(2x - 6) = 4·(4x + 3) + 11
4·(8x - 7) + 4·(8x + 8) = 2·(7x + 7) - 17 -4·(4x - 2) - 2·(4x - 2) = 4·(4x + 3) - 17